Identifikasi Plat Kendaraan Berbasis Aplikasi Python - Putra, Rezki Dwi; Suwardoyo, Untung (Jurnal Sintaks Logika, 2024)
Detecting motor vehicle plates is currently manual and does not utilize technology to determine the identity of vehicle ownership. This research aims to test an application that can identify the identity of vehicle ownership. The type of research used is descriptive, using a Python-based programming application. The research results show that the plate detection accuracy rate is 80% for reading objects at a distance of 10 cm to 40 cm.